The future of the future foods: understandings from the past towards SDG-2 - Mehvish Habib; Sakshi Singh; Shumaila Jan; Kulsum Jan; Khalid Bashir (npj Science of Food)
Abstract Food security faces growing challenges due to population growth, resource limitations, economic pressures, and industrialization-induced lifestyle changes. Traditional food systems struggle to adapt, necessitating innovative solutions and sustainable practices to meet future food demands. This review article explores emerging food system models and alternative food sources, including edible insects, seaweeds, plant-based and lab-cultured meats, underutilized crops, hydroponics, and next-generation fish farming. It highlights the role of food processing technologies such as blockchain, biotechnology, and robotics in enhancing sustainability, reducing waste, and improving food system efficiency. Consumer acceptance of engineered and fortified foods emerges as a critical factor in driving these innovations. The review also emphasizes the need for a transformative approach to food production, incorporating innovative technologies and sustainable practices to ensure food security by 2050. A coordinated effort to integrate alternate food sources and advanced processing methods will be vital for achieving a secure and sustainable global food future.